Perilaku Caregiver Keluarga dalam Merawat Klien Pasca Stroke dan Faktor yang Berhubungan - Husni, Husni; Asmawati, Asmawati; dharma, Kelana Kusuma (Poltekkes Kemenkes Bengkulu, 2024)
Stroke sufferers need long-term recovery after hospitalization due to disability and need assistant of other people (caregiver) to help their lives. The purpose of the research is to describe the duration of care, knowledge, and attitude of the caregiver on the caring skills the stroke survivor. This type of research is descriptive with a cross sectional approach. The sample in this study was a caregiver who was at least 16 years old, had experience in caring, lived in a home with the affected and could read the writing, live in the Bengkulu and Siantan Hulu City. Data of knowledge, attitudes and actions is obtained through a written test with filling out a questionnaire. Data analysis using the Chi-Square test. The results showed that there was no correlation between the length of treatment and the skill of care (p value 0.579), there was a correlation between knowledge on skill (p value 0.012) and there was a correlational between attitude on skill of care stroke survivor (p value 0.023). It is hoped that the Puskesmas can improve the knowledge, attitudes and skills of caregivers in caring stroke survivors through educational programmes